Nicotinic α7 receptors on cholinergic neurons in the striatum mediate cocaine-reinforcement, but not food reward - Fritz, Michael; Rosa, Priscila Batista; Wilhelms, Daniel; Jaarola, Maarit; Ruud, Johan; Engblom, David; Klawonn, Anna M. (Frontiers in Molecular Neuroscience, 2025)
The neurotransmitter acetylcholine has since long been implicated in reward learning and drug addiction. However, the role of specific cholinergic receptor subtypes on different neuronal populations remain elusive. Here, we studied the function of nicotinic acetylcholinergic alpha 7 receptors (α7 nAChRs) in cocaine and food-enforced behaviors. We found that global deletion of α7 nAChRs in mice attenuates cocaine seeking in a Pavlovian conditioned place preference paradigm and decreases operant responding to cocaine in a runway task and in self-administration, without influencing responding to palatable food. This effect can be attributed to alpha 7 receptor signaling in the striatum, as selective deletion of striatal α7 nAChRs using a viral vector approach resulted in a similar decrease in cocaine-preference as that of global deletion. To investigate which type of striatal neurons are responsible for this effect, we selectively targeted Cholinergic (ChAT-expressing) neurons and dopamine D1-receptor (D1R) expressing neurons. Mice with conditional deletion of α7 nAChRs in ChAT-neurons (α7 nAChR-ChATCre) exhibited decreased cocaine place preference and intact place preference for food, while α7 nAChR-D1RCre mice had no changes in reward learning to neither food nor cocaine. Cocaine induction of striatal immediate early gene expression of cFos, FosB, Arc and EGR2 was blocked in α7 nAChR-ChATCre mice, demonstrating the importance of α7 nAChRs on cholinergic neurons for striatal neuronal activity changes. Collectively, our findings show that α7 nAChRs on cholinergic interneurons in the striatum are pivotal for learning processes related to cocaine, but not food reward.